2014
DOI: 10.1021/am506771e
|View full text |Cite
|
Sign up to set email alerts
|

Root-Cause Failure Analysis of Photocurrent Loss in Polythiophene:Fullerene-Based Inverted Solar Cells

Abstract: Metal oxide transport layers have played a crucial role in recent progress in organic photovoltaic (OPV) device stability. Here, we measure the stability of inverted and encapsulated polythiophene:fullerene cells with MoO3/Ag/Al composite anode in operational conditions combining solar radiation and 65 °C. Performance loss of over 50% in the first 100 h of the aging is dominated by a drop in the short-circuit current (Jsc). We reveal a concurrent loss in reflectance from 85% to 50% above 650 nm, which is below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…This is possibly due to the diffusion of Al through the silver, as was reported recently in a different study. [ 45 ] In the dark tests, devices with PEDOT:PSS appear more frequently, yet they signifi cantly underperform compared to the PEDOT:PSS-free samples. In addition, the majority of the dark tests have winning samples that utilize Ag or Au instead of Al.…”
Section: Role Of the Photoactive Layermentioning
confidence: 95%
See 1 more Smart Citation
“…This is possibly due to the diffusion of Al through the silver, as was reported recently in a different study. [ 45 ] In the dark tests, devices with PEDOT:PSS appear more frequently, yet they signifi cantly underperform compared to the PEDOT:PSS-free samples. In addition, the majority of the dark tests have winning samples that utilize Ag or Au instead of Al.…”
Section: Role Of the Photoactive Layermentioning
confidence: 95%
“…It is important to note that the samples where the top Al electrode is directly applied onto the PAL show similar lifetimes under illumination independent of whether the device is encapsulated or not ( Figure 5 b,d). This suggests that, despite the elimination of oxygen and water, the Al/PAL interface remains detrimental to the performance of the device [ 45 ] The results of the device geometry analysis suggest that when considering real operational (outdoor) conditions in an environment with the presence of humidity, oxygen and light, both normal (Al) and inverted (Ag or Au) structures are prone to rapid degradation when unprotected, but can perform equally well when encapsulated.…”
Section: Device Geometry: Normal Versus Invertedmentioning
confidence: 99%
“…Griffin et al have reported that molybdenum oxide releases oxygen under heating, leading to lower molybdenum oxidation states and a shift in the work function. Other authors have shown that molybdenum oxide can negatively interact with the metal anode, thus leading to reduced stability even without illumination …”
Section: Resultsmentioning
confidence: 99%
“…27 Another aspect of the degradation mechanism of inverted OPVs with the aforementioned top electrode was pointed out by Rösch et al through different imaging techniques, whereby they attributed the failure to the migration of silver and diffusion into the MoO 3 layer, changing its work function. 28 Greenbank et al also discuss diffusion into the active layer, and its resulting weakening is correlated to the decline (specifically J sc reduction) in the device performance when used in conjunction with MoO 3 as the HTL.…”
Section: Introductionmentioning
confidence: 98%